2011
DOI: 10.1021/es202874p
|View full text |Cite
|
Sign up to set email alerts
|

Phages of Bacteroides (GB-124): A Novel Tool for Viral Waterborne Disease Control?

Abstract: Current fecal indicator bacteria (FIB) and emerging microbial source tracking (MST) methods may indicate the presence and even the likely source of water contamination, but they are less effective at determining the potential risk to health from human enteric viruses. This paper investigates the presence of human-specific phages (detected using a low-cost MST method) in municipal wastewaters (MW) and assesses whether they may be used effectively to screen for the likely presence of human adenovirus (HAdV) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 52 publications
7
40
0
Order By: Relevance
“…GB‐124 phages, however, were not detected in any of the nonhuman faecal samples analysed (Table ), which is consistent with earlier findings from the EU (Ebdon et al . , ; Ogilvie et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GB‐124 phages, however, were not detected in any of the nonhuman faecal samples analysed (Table ), which is consistent with earlier findings from the EU (Ebdon et al . , ; Ogilvie et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…However, considering that phage was not detected in any nonhuman faecal samples in the EU (Ebdon et al . , ; Ogilvie et al . ) and that it was detected in more known human samples than any other viral marker tested in the California study (Harwood et al .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, phages may be a more appropriate indicator of the presence of enteric viruses in water and wastewaters than the bacterial indicators that continue to be widely used (Jofre et al, 1986;Gantzer et al, 1998;Purnell et al, 2011;Ebdon et al, 2012;Jofre et al, 2014) et al (2013) demonstrated that reductions in levels of somatic coliphages and F-RNA specific phages were 2.7 and 1.7 log higher as a result of MBR treatment than by conventional activated sludge treatment. Zanetti et al (2010) observed that, despite the smaller diameter of F-RNA specific phages (21-30nm), their levels in the permeate were lower than those of somatic coliphages (30-100nm).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, these standards (27)(28)(29)(30) have succeeded in reducing many types of shellfishrelated bacterial outbreaks; however, it has been shown that the bacterial standards are inadequate for estimating the presence of enteric viruses in shellfish and growing waters. Moreover, the depuration process for shellfish harvested from conditionally approved (or category B) growing areas has been shown to be less effective at eliminating enteric viruses than bacteria from contaminated shellfish (31)(32)(33).…”
mentioning
confidence: 99%